The development of a micro-scale turbine-generator and its potential application to develop a micro-scale and cost-effective ORC power plant - Hernandez Carrillo, Isaias (2020)
In the context of a sustainable future, distributed power will become increasingly relevant to satisfy the demand for heat and power of the domestic sectors, which are energy-intensive and suffer from low efficiency and hence waste heat. Although several technologies are available to convert this waste heat into power, the organic Rankine cycle (ORC) is advantageous in terms of maturity, versatility and simplicity. However, for microscale, it can often be uneconomical, due to the required investment cost of an expander. In this thesis the following research question is proposed: How can the techno-economic performance of a micro-capacity ORC expander be improved? To address this question, a micro-turbo-generator (MTG) was developed following the product design method. This consisted of four main tasks: an exploration of the need, design, testing and assessment of feasibility. During the investigation of the need, polymeric structural components, an outer enclosure and a limited expansion control were the three features proposed for addressing key needs of the MTG-ORC. For the design, two activities were performed: conceptual design and analysis. The conceptual design consisted of the definition of the cycle and the architecture of the MTG-ORC as well as the design/selection of its components (turbine, generator, control and outer enclosure). The analysis is comprised of a simulation of the thermo-aerodynamic performance, an analysis of the fluid-structure interaction and an analysis of the chemical compatibility between materials and working fluids. The testing involved the fabrication of a prototype, the construction of a test rig and the experimentation of the unit with compressed air as the working fluid. During this test, the performance of polymeric components was assessed and compared with their metal counterparts. The results shown that, according to the simulations, the unit presents a comparable performance regardless of the working fluid used (idealised-R245fa, real-R245fa and air). This allows the prediction of performance of the unit working with R245fa using two different methods: a performance simulation with real-R245fa and a test with air combined with the dynamic similarity principle. With these two methods, the performance of the unit working with R245fa at peak thermo-aerodynamic efficiency showed respective results of: efficiency 0.7-0.7, rotational speed 33200[rpm]-30100[rpm], mass flowrate 0.22[kg/s]-0.2[kg/s] and thermo-aerodynamic power 1.3[kW]-1.2[kW]. An examination of these results revealed consistency between the two methods, which proves that dynamic similarity principle is valid for this investigation. Additionally, the implementation of polymeric components seems feasible in terms of thermo-aerodynamic performance, mechanical strength and chemical compatibility. This became the principal advancement in this investigation. However, a test of these components with refrigerant is yet to be conducted when the resources become available. The results also indicated that the polymeric components do not show a significant difference on the thermo-aerodynamic performance with respect to their aluminium counterparts with a statistical significance of p=0.05; therefore, they can be a solution to reduce the power/weight ratio of the MTG whilst maintaining competitive performance. Moreover, they can potentially reduce the production cost of components. In contrast, although the outer enclosure and the limited expansion seem to be theoretically feasible, they are yet to be experimentally validated. The results of this investigation are expected to lay a firm foundation to recommend the implementation of polymeric components into expanders and other elements of small/micro-scale ORC and refrigeration systems in the future.